(The)firekeeper's son - Park, Linda Sue. (Clarion Books, 2004)
In eighteenth-century Korea, after Sang-hee's father injures his ankle, Sang-hee attempts to take over the task of lighting the evening fire which signals to the palace that all is well. Includes historical notes.